CAMEL MILK - FEATURE, APPLICATION (Proceedings of International Educators Conference, 2024)
Camel milk is a traditional drink of the Eastern countries, which is not only tasty, but also rich in nutrients. The taste is sweet, but it directly depends on the quality of water and food given to the camel. Also, among its characteristic features, it can be distinguished that it foams easily when poured and is thicker than other animal milks.Benefits and harms of camel milk